Physical fitness mediates and predicts for high blood pressure among children in relation to weight status - Chuang, Hai-Hua; Cherng, Wen-Jin; Lin, Chih-Hung; Lee, Li-Ang; Hsu, Kuang-Hung; Lin, Rong-Ho (Frontiers in Public Health, 2023)
Background: Pediatric hypertension contributes to adulthood hypertension and target organ damage. Obesity is a well-known predictor for pediatric hypertension; however, the relationship between physical fitness and blood pressure (BP) is unclear among children. This study aimed to compare the differences in demographics, anthropometrics, and physical fitness across BP subgroups and investigate whether physical fitness was related to pediatric hypertension independent of weight status. Methods: This quantitative, cross-sectional study investigated demographic, anthropometric, physical fitness, and BP measures among 360 healthy school-aged children. Continuous variables were compared across BP subgroups with the one-way analysis of variance. Mediation and moderation analyses were used to explore the mechanism. Multivariable regression models were used to assess independent associations for hypertension. Results: There were 177 (49.2%), 37 (10.3%) and 146 (40.6%) children in the normotensive, elevated BP and hypertensive subgroups, respectively. The hypertensive subgroup had higher body mass index (BMI) and waist/height ratio percentiles and performed worse in 800-m run, standing long jump (SLJ) and 1-minute sit-ups than the normotensive subgroup did. Furthermore, 800-m run percentile (total effect: β = 0.308, standard error = 0.044, p < 0.001) and sit and reach percentile (total effect: β = 0.308, standard error = 0.044, p < 0.001) mediated the relationship between BMI percentile and systolic BP percentile; SLJ percentile was directly associated with diastolic BP percentile (β, -0.197, 95% confidence interval, -0.298–-0.097; p < 0.001). The parsimonious model of multivariable regression models revealed that the SLJ percentile (adjusted exp (β), 0.992, 95% confidence interval, 0.985–0.999; p = 0.042) and BMI percentile (adjusted exp (β), 1.024, 95% confidence interval, 1.016–1.032; p < 0.001) were two independent predictors for pediatric hypertension. Conclusions: Physical fitness mediates the relationship between anthropometric and BP measures. SLJ percentile is associated with pediatric hypertension independent of the BMI percentile. Proactive screening and health promotion on not only healthy weight status but also good physical fitness may be beneficial for BP control among school-aged students.